2018
DOI: 10.1080/13573322.2018.1554562
|View full text |Cite
|
Sign up to set email alerts
|

Performance pedagogy at play: pupils perspectives on primary PE

Abstract: Physical education (PE) in England, has historically been and is increasingly seen as a subject in which political agendas can and are being enacted (Penney, 2008) as health, sport and /or leisure agendas compete for space against educational aspirations (Houlihan and Green, 2006). Against this backdrop, in 2012, the UK Government announced the launch of 'Primary PE and Sport Premium' (PPESP) funding (amounting to £450 million) for English primary schools, initially for three years (although later extended). D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 37 publications
0
8
0
1
Order By: Relevance
“…Profiles combining high mastery goals and high performance or performance-approach goals partly also show an expedient character. However, any productive integration of these results into everyday school PE practice seems partially questionable due to an at least partially prevalent performance-pedagogical attitude of PE teachers and a popular PE-orientation toward sports, competition, and social comparison (e.g., Wolters, 2012;Coulter and Chróinín, 2013;Svendsen and Svendsen, 2016;Schierz and Serwe-Pandrick, 2018;Stirrup, 2018). For a practical meaning of these justifying results, a change of this basic PE-teacher habitus therefore seems to be both indispensable and promising.…”
Section: Resultsmentioning
confidence: 99%
“…Profiles combining high mastery goals and high performance or performance-approach goals partly also show an expedient character. However, any productive integration of these results into everyday school PE practice seems partially questionable due to an at least partially prevalent performance-pedagogical attitude of PE teachers and a popular PE-orientation toward sports, competition, and social comparison (e.g., Wolters, 2012;Coulter and Chróinín, 2013;Svendsen and Svendsen, 2016;Schierz and Serwe-Pandrick, 2018;Stirrup, 2018). For a practical meaning of these justifying results, a change of this basic PE-teacher habitus therefore seems to be both indispensable and promising.…”
Section: Resultsmentioning
confidence: 99%
“…Sarah's strong emphasis upon practical performance and ad-hoc attempts to impart social and cognitive learning appears to support a Cartesian dualism -a view that the body is the 'doer' and the mind is the 'thinker' (Quennerstedt 2013;Grankvist, Kajonius and Persson 2016). In seeing the body and mind as separated, she may have felt her piecemeal attempts at developing pupils' holistic learning would stimulate the pupils' otherwise disconnected minds (Stirrup 2020). Such 'add-ons' may have also provided additional content to ensure she could 'teach' for the full duration of the lesson.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Lleras (2008) found that participation in sports activities was associated with higher educational attainment and job earnings. Despite this, in a recent case study Stirrup (2018) highlighted that coaches, who were involved in delivering extracurricular clubs, fostered a competitive environment to ensure the school was able to perform to a high standard at school fixtures and competitions. This meant pupils were purposefully selected for the clubs and pupils who wanted to attend but did not perform to the desired standard were rejected.…”
Section: Discussionmentioning
confidence: 99%